2020
DOI: 10.25081/jmb.2020.v4.6389
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal uses of plants by major ethnic groups of Hilly Districts in Nepal: A review

Abstract: Plants are used as ethnomedicine by indigenous people living all around the world. In Nepal, plants are being used for healing diseases since a long period by various ethnic groups of rural areas due to difficulty in the availability of modern medicines. Many researchers have contributed to the documentation of ethnomedicinal knowledge on plants in Nepal; however few studies have been carried out on hilly districts. Our study aims to review and compile all the published research documents on ethnomedicinal use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…5). This distribution of applications is in accordance with other studies, e.g., Kaur et al (2020), Miya et al (2020) from the Indian sub-continent and Monigatti et al (2013) reported from Peru.…”
Section: Disease Curedsupporting
confidence: 93%
“…5). This distribution of applications is in accordance with other studies, e.g., Kaur et al (2020), Miya et al (2020) from the Indian sub-continent and Monigatti et al (2013) reported from Peru.…”
Section: Disease Curedsupporting
confidence: 93%
“…Also, the nested plots of 3m x 3m and 1m x 1m within the 10m x10m plot were laid on the lower right-hand side corner for shrubs and herbs observation, respectively (Dongol, 2002). Secondary data were collected from online portals like Google scholar and Research gate (Gautam et al, 2020;Timilsina et al, 2020;Miya et al, 2020). Aquatic floral species were not studied due to inaccessibility to the water bodies.…”
Section: Data Collectionmentioning
confidence: 99%
“…Traditional plantbased medicines are used by 70% of India's population (Gadgil, 1998), 80% of Pakistan's population (Ahmad and Ghafoor, 2000), and 80% of Nepal's population (Kunwar et al, 2006). It is estimated that almost 17% of the population lives in cities and has access to modern medicine, while the rest of the population still relies on traditional medicine for their basic health care requirements in Nepal (Ambu et al, 2020;Adhikari et al, 2019) In the hilly regions of Nepal, about 215 types of plants are used to cure 139 different types of diseases (Miya et al, 2020).…”
Section: Traditional Medicine In Nepalmentioning
confidence: 99%